Software engineer Islamic ethics : an interactive web-based model - Hameed, Shihab A.; Al-Khateeb, Khalid A. Saeed; Mutaz, Zubayda (2010)
Computer-based applications required qualified software engineers professionally and ethically. Software engineering professionals are facing several ethical-related problems which are costly, harmful and affected high ratio of people. Professional organizations work very hard to establish codes of ethics to help software engineering professionals to understand and manage their ethical responsibilities. Islam considers ethics as an essential factor to build individuals, communities and society. Islamic ethics are set of moral principles and guidance that recognizes what is right behavior from wrong. It is universal, comprehensive, stable, fair, and historically prove success in building ethically great society. Muslims' software engineers and professionals should have an effective role in software development. They have to understand ethics and implement it in their work. This research paper shows the main phases for solving such problem. It focuses mainly on adopting an enhanced version of software engineering principle based on Islamic ethical values. Web-base database model for Islamic ethics are developed and sample of results are presented.